Spousal characteristics and its effect on life insurance ownership in Singapore. - Kiew, Hongsheng. (2008)
This project explores whether there are differences in life insurance ownership between spouses in a family and assesses how these disparities are caused by differences in characteristics of their opposite spouses. Here, life insurance ownership refers to both amount insured and also the number of policies owned.